Remote sensing of the increase in protected agriculture and the factors that have driven it in San Salvador el Verde, Puebla (2010-2022) - Sánchez Olarte, J.; Guevara Brindis, J.; Méndez Espinoza, J. A. (RIIIT Revista Internacional de Investigación e Innovación Tecnológica, 2026)
Currently, protected agriculture is used to optimize the available space for cultivation, where vegetables, fruits, and flowers can be grown, with a focus on marketing these products. In the case of San Salvador el Verde, Puebla, greenhouse floriculture has grown; however, the factors that have led to an increase in these structures and the number that exist are unknown. The objective was to conduct remote sensing of the increase in greenhouses in 2010, 2015, 2020, and 2022 and to identify the entrepreneurial factors that motivate producers to engage in floriculture in this municipality. A mixed-methods approach was used: interviews were conducted with three groups of producers, and the free geographic information system (GIS) software QGIS was used for remote sensing of greenhouses. Among the most notable results, the key factors that favored the increase or expansion of structures were affordable greenhouse construction costs, government support, and the influence of cultural diversity, which contributed to growth from 231 greenhouses reported by INEGI in 2010 to 855 greenhouses identified through remote sensing in 2022 using QGIS.
Keywords: QGIS; entrepreneurship; INEGI; SIAP; geographic information systems.